Tinjauan Yuridis Eksistensi Putusan Homologasi Ditinjau dari Teori Kepastian Hukum - Darell Tri Jaya; Ida Kurnia (Jurnal Hukum Lex Generalis, 2024)
In people's lives, it will be inseparable from the activities of agreements, one of which is borrowing as stipulated in Article 1754 of the Civil Code. The party who lends funds or creditors and the party who borrows funds or debtors at one time may experience the problem of late payment. Therefore, in the event of bankruptcy, the debtor has the opportunity to apply for a postponement of payment through the homologation decision mechanism ratified by the Commercial Court. As a normative juridical research, this research focuses on the study of the law accompanied by an analysis of the understanding of reading books Thus, later the writing of this journal will be able to answer how the existence of homologation decisions is reviewed from Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations accompanied by a study of the theory of legal certainty as a form of protection both for debtors but also for creditors.